2020
DOI: 10.1039/c9an01339c
|View full text |Cite
|
Sign up to set email alerts
|

Engineering anisotropic cardiac monolayers on microelectrode arrays for non-invasive analyses of electrophysiological properties

Abstract: Engineering cardiac tissues with physiological architectural and mechanical properties on microelectrode arrays enables long term culture and non-invasive collection of electrophysiological readouts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…In another work, a microelectrode array platform was fabricated for recording the beating rate and conductive velocity of cardiomyocytes. In this device, the cardiac monolayer beat in a synchronized fashion, and the conduction velocity was close to the physiological value [208]. Different methods can measure the beating of heart tissue.…”
Section: Implementation Of Physical Forcesmentioning
confidence: 75%
“…In another work, a microelectrode array platform was fabricated for recording the beating rate and conductive velocity of cardiomyocytes. In this device, the cardiac monolayer beat in a synchronized fashion, and the conduction velocity was close to the physiological value [208]. Different methods can measure the beating of heart tissue.…”
Section: Implementation Of Physical Forcesmentioning
confidence: 75%
“…This arrhythmogenic behavior of the corrected CMs was replicated with CMs derived from the hESC H9 control line. MEA measurements on fibronectin coated glass substrate have been reported to cause more beating variation, compared to more ideal culture systems such as hydrogels 48 , that more closely resemble the in vivo extracellular environment. Since the ECM is assumed to be abnormal in MFS, it could be suggested that the MFS CMs receive less mechanical feedback signals from the environment, explaining the small amount of variation in beat rate 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Disease modeling can be achieved by manipulating the mechanical properties of the biomaterials employed, including extracellular matrix hydrogels [128] or synthetic fibers, which impact on cell attachment, alignment and stiffness [129]. Moreover, cardiac cells can be integrated in microfluidic devices that recapitulate in vivo microenvironment complexity, including electrical stimulation, cyclic stretch, fluid flow and chemical gradients generation [129].…”
Section: Cultured Cell-based Approaches To Study Cardiac Intercellular Communicationmentioning
confidence: 99%